Soil Contamination of Public Places with Toxocara spp. Egg in Kermanshah, Iran, in 2014 - Maleki, Bahman; Seyyed Tabaei, Seyyed Javad; Tahvildar, Farid; Khorshidi, Ali (Novelty in Biomedicine, 2016)
Background: Toxocariasis is considered as an important neglected tropical disease. Although, the prevalence of Toxocara eggs in soil has previously been reported in different parts of Iran, the extent of this condition is not precisely known in Kermanshah city, west of Iran. Materials and Methods: A total of 126 soil samples were collected from different zones of Kermanshah public places during April-June 2014. The samples were examined for Toxocara spp. eggs via modified floatation method using sodium nitrate (NaNO3) and the data was analyzed using Data Analysis and Statistical Software (STATA Ver.13.1). Results: Toxocara spp. eggs were found in 17 (13.5%) out of 126 samples collected from the studied areas. There was a significant difference between contamination rate in the areas with low levels of health status and that in the areas with high levels (p=0.003). Conclusion: According to the results obtained in the present study public parks, streets, and squares of Kermanshah are contaminated with eggs of Toxocara spp. Considering these findings, establishment of a wisely planned health program for controlling helminthes in the soil and the population of the stray dogs and cats in order to reduce the distribution of parasitosis is strongly recommended.